Asymmetric dimethylarginine but not osteoprotegerin correlates with disease severity in patients with moderate‐to‐severe psoriasis undergoing anti‐tumor necrosis factor‐α therapy. Issue 4 (14th September 2015) - Pina, Trinitario; Genre, Fernanda; Lopez‐Mejias, Raquel; Armesto, Susana; Ubilla, Begoña; Mijares, Veronica; Dierssen‐Sotos, Trinidad; Corrales, Alfonso; Gonzalez‐Lopez, Marcos A.; Gonzalez‐Vela, Maria C.; Blanco, Ricardo; Hernández, Jose L.; et al.
Abstract: Patients with psoriasis, in particular those with severe disease, have an increased risk of cardiovascular (CV) events compared with the general population. The aim of the present study is to determine whether correlation between asymmetric dimethylarginine (ADMA) and osteoprotegerin (OPG), two biomarkers associated with CV disease, and disease severity may exist in patients with moderate‐to‐severe psoriasis. We also aimed to establish if baseline serum levels of these two biomarkers could correlate with the degree of change in the clinical parameters of disease severity following the use of anti‐tumor necrosis factor (TNF)‐α therapy in these patients. This was a prospective study on a series of consecutive non‐diabetic patients with moderate‐to‐severe psoriasis who completed 6 months of therapy with anti‐TNF‐α‐adalimumab. Patients with kidney disease, hypertension or body mass index of 35 kg/m 2 or more were excluded. Metabolic and clinical evaluation was performed immediately prior to the onset of treatment and at month 6. Twenty‐nine patients were assessed. Unlike OPG, a significant positive correlation between ADMA and resistin serum levels was found at the onset of adalimumab and also after 6 months of biologic therapy. We also observed a positive correlation between the percent of body surface area affected (BSA) and ADMA levels obtained before the onset of adalimumab and a negative correlation between baseline ADMA levels and a 6‐month BSA change compared with baseline results. In patients with moderate‐to‐severe psoriasis, ADMA levels correlate with clinical markers of disease severity.